The removal of Zinc, Chromium and Nickel from industrial waste water using Rice husk - Majeed, Majid; Muhammed, Ali; Rasheed, Khalid (Iraqi Journal of Science, 2023)
The aim of this study was to use low cost adsorbents, which consists of plant wastes in treatment of Industrial waste water by fixed bed column technique and study the effect of to two variables (pH value and contact time) on adsorption process. The sample of plant waste (Rice husk) was tested to determine its activity which gives the best performance in heavy metals removal and other pollutants (TSS, TDS and COD). Adsorption tests showed all tested plant adsorbents had significant heavy metal removal efficiency. The best removal efficiency 96.56% of Cr was occurred at pH 6.5 and 5hrs. Higher removal efficiency 99.02% of Ni was occurred at pH 6.5 and 0.15hr. While, lower removal efficiency 94% for Zn obtained at pH 5 and 2.83hrs. Removal efficiency for TDS, TSS and COD were 58.6%, 98.8% and 86.6% respectively.